REKONSTRUKSI PEMBELAJARAN SEJARAH MELALUI PROJEK BASED LEARNING (PjBL) di SMA SAINTEK BS UHAMKA - Hari Naredi; Ahmad Ruslan; wardahsamiah (Universitas PGRI Yogyakarta, 2023)
This study aims to examine the innovations needed by history learning in the face of negative stigma regarding history learning which is considered